Evaluating the impact of photo order on perceptions of crowding at Buffalo National River - Cribbs, Tyler William (Kansas State University, 2018)
Visual-based methods are vital tools within outdoor recreation management. This method allows researchers to develop an empirical evaluation of social norms of outdoor recreationists. To better understand visitor’s perceptions, and provide usable information to site managers, researchers must better understand their methodology. This study assessed whether photograph order, within a visually-based method, in a field setting, creates differential results relative to a lab setting by comparing our results to previous literature. To accomplish this, a study was conducted at Buffalo National River (BUFF), Arkansas, USA. Visual-based methods were used in a field setting to determine whether there are order effects in perceptions of crowding between sequential and non-sequential photograph presentation order. Results indicated that study setting may influence whether order effects are present. This research will contribute to the growing body of work in the study of research methods for protected area and visitor use management.
Keywords: photographs; social norms; visitor use management; visual-based methodscrowding